Analysis Management of Ornamental Plant Care on The Asri Taman and Sanggar Indah Jaya Store in Cempaka Putih Sub-District - Imam Safir Alwan Nurza (Risenologi, 2020)
Management of ornamental plant care is regulated on how to care for ornamental plants both in the form of herbs and succulents nor woody plants such as shrubs and trees, so that it can produce quality ornamental plants. The research purpose was to find out the management of ornamental plant care on Asri Taman and Sanggar Indah Jaya stores. The plant store population found there are four shops until the samples can be taken are two shops. The sampling technique used to random sampling which takes a random sample from the population. Data collection techniques by interview and observation. Interview with information from sources related to the management of ornamental plant care in the store. Observation by observing ornamental plants both in the form of herbs and succulents nor woody such as shrubs and trees. The research resulted that Asri Taman and Sanggar Indah Jaya stores that are very good in regulating watering, fertilizing, and giving pesticides in ornamental gardens which are indicated by green leaves, not wilting, and not growing adventitious roots on the stem, so that it can produce quality ornamental plants.